2020
DOI: 10.1002/pen.25384
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of carbon nanotube and nanoclay on thermal properties and flammability behavior of amorphous polyamide/SEBS blend

Abstract: Multiwall carbon nanotubes (CNT) or montmorillonite clay (MMT‐30B) were added to a poly(hexamethylene isophthalamide‐co‐terephthalamine) (an amorphous polyamide ‐ aPA) and styrene‐ethylene/butylene‐styrene graphitized with maleic anhydride (SEBS) blend, in different concentrations, in order to investigate the morphology, thermal properties and flammability behavior. Different nanoparticle localizations in the phase blend were observed through transmission electronic microscopy. CNT nanoparticles are localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Besides, the char formed on the 1% CNT sample surface is quite different from that in the samples containing MMT‐30B (Figure 7). In a previous work, [ 22 ] even without the formation of a CNT network structure, a V‐2 classification was obtained for nanocomposites of aPA/SEBS and 0.5% and 1.0% of nanoparticles. The difference between the results obtained there and the ones in the present study can be related to the CNT location on the polymeric blend.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides, the char formed on the 1% CNT sample surface is quite different from that in the samples containing MMT‐30B (Figure 7). In a previous work, [ 22 ] even without the formation of a CNT network structure, a V‐2 classification was obtained for nanocomposites of aPA/SEBS and 0.5% and 1.0% of nanoparticles. The difference between the results obtained there and the ones in the present study can be related to the CNT location on the polymeric blend.…”
Section: Resultsmentioning
confidence: 96%
“…The difference between the results obtained there and the ones in the present study can be related to the CNT location on the polymeric blend. In the work of Paes et al, [ 22 ] the CNTs were preferentially located in the SEBS phase, which burns first and rapidly. However, in this work, the CNTs were located in the aPA phase (Figure 1D–F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, numerous researchers have reported many studies in the literature and conducted comprehensive review on the combination of conventional FR fillers with a nanomaterial filler into the polymer matrix to improve polymer flame retardancy properties. 37,38 For instance, Chen et al 39 investigated the flame retardancy performance of polypropylene (PP) filled with graphene nanoplatelets (GNP) and MAH and found that increasing GNP content improved flame retardancy property of neat PP. Similarly, the performance of GNP as FR to improve the fire retardant ability of PE/ATH composite has been studied, 19 while Liu 14 reported the study of using PE blended with MAH and montmorillonite (MMT) nanoclay.…”
Section: Introductionmentioning
confidence: 99%
“…It has the elasticity of rubber at room temperature and plasticity at high temperatures . Moreover, it can be produced by injection molding, extrusion molding, blow molding, and other processing methods. , Due to their excellent aging resistance, insulativity, and mechanical properties, polystyrene-based thermoplastic elastomers (TPE-S) composed of poly­(styrene-ethylene-butylene-styrene) (SEBS), white oil, and polypropylene (PP) are widely used in electric wire and cable, construction, and automobile industries. However, because of their high flammability, the applications of TPE-S in other industries are greatly limited. Therefore, it is particularly urgent to improve the flame retardancy of the TPE-S.…”
Section: Introductionmentioning
confidence: 99%